Mediation role of perceived social support and burnout on financial satisfaction and turnover intention in primary care providers: a cross-sectional study - Huosheng Yan; Lingzhi Sang; Hongzhang Liu; Cancan Li; Zijing Wang; Ren Chen; Hong Ding; Zhi Hu; Guimei Chen (BMC, 2021)
Abstract Background Turnover intention is a major cause of reduced team morale and low work efficiency. It hinders work performance and reduces the quality of medical services. This study aimed to investigate the relationship between financial satisfaction and turnover intention and its mediators among primary care providers. Methods Multi-stage random cluster sampling was used to select 1241 participants from four counties and three districts in Anhui province, China. Data were collected using a self-administered questionnaire. Turnover intention was assessed with a turnover intention assessment scale. Perceived social support and burnout were measured with the 12-item Perceived Social Support Scale and the Chinese version of the Maslach Burnout Inventory, respectively. Structural equation modeling was used for data analysis. Results The findings showed high turnover intention among primary care providers (mean score 14.16 ± 4.337), and most providers reported low financial satisfaction (mean score 2.49 ± 0.990). The mean perceived social support score was 64.93 ± 13.229, and only 6.1% of primary care providers reported no burnout. Compared with participants with high financial satisfaction, those with low financial satisfaction were more likely to report higher turnover intention (β = − 0.216, p < 0.001), less perceived social support (β = 0.181, p < 0.001), and more severe burnout (β = − 0.123, p < 0.05). Turnover intention may be related to perceived social support (β = − 0.147, p < 0.001) and burnout (β = 0.239, p < 0.001). Furthermore, the effect of financial satisfaction on turnover intention was significantly mediated by perceived social support (β = − 0.027, p < 0.001) and burnout (β = − 0.029, p < 0.05). Conclusions Turnover intention is associated with financial satisfaction, with this association mediated by perceived social support and burnout. A reasonable mechanism needs to be established to improve financial satisfaction and perceived social support and reduce burnout among primary care providers.